A new view of the Bubnov-Galerkin method in the linearization context - Dong Anh, Nguyen; Elishakoff, I. (Vietnam Journal of Mechanics, 2012)
In the study an extension of the Bubnov-Galerkin method in terms of the equivalent linearization method is presented. It is combined with sequential linearization and nonlinear procedure to yield a new method for solving nonlinear equations which can improve the accuracy when the nonlinearity is strong. For illustration the Duffing oscillator is considered to show the effectiveness of the proposed method.